POTENSI RISIKO LINGKUNGAN PAPARAN HIDROGEN SULFIDA BAGI MASYARAKAT PINGGIRAN SUNGAI TAWAR PALEMBANG - Suci Ambarwati; Yustini Ardillah (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2021)
Settlements in the edge of the Tawar River Kelurahan 29 Ilir Palembang City is a slum. A buildup of garbage in the Tawar River openly lead to gas the results of the decomposition process such as Hydrogen Sulfide gas (H2S) off into the air which cause the air surrounding settlements into the smell. This study aims to determine the analysis of the environmental health risk of exposure to H2S in society the slums along the Tawar River City of Palembang. This research is descriptive research using quantitative analysis. This study uses analysis study environmental health risk with the analysis of univariate and bivariate. The sample in this study were 92 respondents with the sampling technique using purposive sampling. The measurement results show the average concentration of H2S in the air 0.0019 mg/m3 which is still below the threshold value set the Decision of the Minister of Environment No. 50 Year 1996 on the raw level, the smell of H2S that 0,028 mg/ m3. The results of the risk analysis showed that there were 35 respondents (38%) which has the value of RQ>1 for exposure realtime. As for the exposure to the lifetime of all respondents (100%) has the value of RQ>1, which means that it has a huge risk of not safe so it is required to perform risk management. Suggestion of this research should community increase a healthy lifestyle by eating vegetables, fruits, vitamins and honey as well as exercise to improve immunity. The public are advised to install the air purifier of the house and multiply your plants barrier properties can reduce the level of pollutants in the air and plant trees to minimize the smell that is produced by H2S gas such as boxwood tree and American holly.